Efektivitas Layanan Konseling Kelompok Dengan Teknik Homework Assignment Untuk Meningkatkan Tanggungjawab Belajar - Safira, Nabila Atari; Siregar, Alfin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to analyze the effectiveness of group counseling services using the Homework Assignment technique approach to increase student learning responsibility at SMA Negeri 7 Medan. This research used quantitative experimental methods. This research involved 56 class X students and a sample of 8 people who were selected using purposive sampling. The research design uses pre-experiment pretest-posttest. The results of data analysis using the Wilcoxon Signed Ranks test showed asymp significance. sig (2-tailed) of 0.012 is lower than the specified significance level (0.05). Thus, the Homework Assignment technique through counseling services has proven to be effective in increasing student learning responsibility